Chapitres invisibles dans Lupus et Aâma de Frederik Peeters - Jacques Dürrenmatt (Cahiers de Narratologie)
Nothing seems to predispose Frederik Peeters to use the chapter to organize his science fiction cycles Lupus and Aâma. However, it is difficult to escape, in the context of the sequential sequence, from a mode of cutting that has found in the graphic novel a new place of experimentation.